THE EFFECT OF MUSK EXTRACTION PROCEDURES ON THE STRESS RESPONSE OF FARMED FOREST MUSK DEER (MOSCHUS BEREZOVSKII) - S. Yang1+; M. Zhang1+; Y. Li; M. Cha; S. Xu; Y. Liu; X. Guo; T. Zhang; M. Shi; S. Liu; D. Hu1; T. Wronski2 (Journal of Animal and Plant Sciences, 2020)
To determine the impact of musk extraction procedures on the endocrine stress response of farmed male forest musk deer and to improve welfare and husbandry conditions in captivity. In our study we measured the effects of musk extraction and related procedures (capture and restraint) on the stress level of treated individuals by analyzing fecal cortisol concentrations (FCC). Fecal samples were collected from 20 captive musk deer for 20 days prior and 28 days after the treatment. Ten animals were subjected to capture, restraint, and extraction (CRE-treatment), another ten experienced only capture and restraint (CR-treatment), but no extraction. Generally, stress levels observed in the CRE group were significantly higher than those of the CR group. In the CRE group, seven individuals significantly increased, but three decreased the FCC after treatment, while in the CR group, eight individuals increased and two decreased the FCC after treatment. However, the FCC recovery time in the CRE group was significantly longer than that of the CR group. Furthermore, musk deer with higher baseline levels were more likely to decrease FCC after handling. Our results suggest that individual personality, the intrinsic stress level and poor habituation to captivity permanently increase baseline FCC, leading to a sensory adaptation of the HPA axis and therefore to a decreased FCC after CRE-treatment.
Keywords: Fecal cortisol concentration; Human handling; Captive breeding; Musk production; Stress hormones; Animal welfare